Lawsonia intracellularis: estudo da transmissão interespécies e da utilização do fluido oral na detecção de imunoglobulinas - Michelle de Paula Gabardo (2015)
This thesis was divided in two studies. The first part of first study aimed to check if mice could be infected by feces from L. intracellularis infected pigs. Thirty-four mice received feces of experimentally infected pigs (C1) and 11 received feces from negative pigs (C2). Mice were test by nested-PCR and immunohistochemistry (IHC). The second aimed to test if pigs could be infected when exposed to infected mice. Twelve pigs received positive mice feces (S1), and 2 received negative mice feces (S2). Pigs were tested by serology, PCR and IHC. C1 mice were nested-PCR positive at least one collection and 3 mice were IHC positive. Ten S1 were PCR positive, 9 seroconverted and 5 were IHC positive. The second study aimed to investigate the presence of IgA and IgG anti-L. intracellularis in oral fluid (OF) samples. Pigs were separate into control (T1) and inoculated groups (T2). Blood and OF samples were collected from each animal and pen. These samples were tested by immunoperoxidase monolayer assay (IPMA) for detection IgG in serum and IgA and IgG in OF. The IPMA showed 84.62% of sensitivity in detection of IgA, 88.46% in IgG in OF and 100% in serum, and specific was 100% in both samples. There was high agreement between the individual and pen OF. In conclusion, this thesis demonstrated that mice may be infect and eliminate the agent in sufficient quantity to infect pigs. And, OF samples might be useful for profiling herds, but on farm experiments are still pending.